Romanian Doctoral Research – Perspectives on International Accounting Harmonization - Rațiu, Raluca Valeria; Tudor, Adriana Tiron (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The purpose of this study is to analyze the interest of Romanian accounting doctoral researchers regarding the process of international accounting harmonization. We analyzed the research outcomes, doctoral dissertations, with the subtopic on international harmonization for the period 2000-2010, from the most important Romanians research and doctoral schools of accounting. The results of our quantitative study confirm our hypothesis, showing that there is an increasing trend concerning the interest in accounting harmonization, and the results of our qualitative study confirm our second hypothesis showing that the research topics represent sensitive issues of the accounting harmonization process. Our findings conclude that the Romanian accounting research environment is in line with the international accounting research environment on the topic of accounting harmonization and its subtopics.